Multimodality Imaging for Rare Presentation of Placenta Increta in the First Trimester in a Patient with Previous Cesarean Section and Asherman Syndrome - Harshna V. Vadvala; Jonathan E. Henning; Abimbola Aina-Mumuney (Journal of Medical Ultrasound, 2024)
We report multi-modality imaging (Ultrasound and Magnetic Resonance Imaging) findings of a rare complication in a multi-gravida patient with history of Asherman syndrome presenting with placenta increta in a cesarean scar ectopic pregnancy. The appropriate diagnosis was established with imaging and patient was managed surgically with total abdominal hysterectomy and bilateral salpingectomy. Asherman syndrome and its management of hysteroscopic adhesiolysis are associated with increased odds of placenta accreta spectrum and postpartum hemorrhage. Patients with Asherman syndrome are considered high risk in pregnancy and should be closely monitored for placental site abnormalities during current and subsequent pregnancies.